Water : science, policy, and management : challenges and opportunities - Lawford, Richard G. (Washington, D.C. : American Geophysical Union, 2003)
From the local to the global scale, water use and sustainability are issues of historic importance. Never before has water science needed to inform water policy so much, and never before have we seen how challenging it is to advance that relationship.
Using science to address a growing worldwide water dilemma for the 21st century -- Urban water issues : an international perspective -- Groundwater issues -- Water development and food production.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Water resources development; Hydrology; Water-supply -- Government policy; Water-supply -- Management; Electronic books